Insect pollinators of the late winter flowering Rhamnus alaternus L., a candidate for honeybee-friendly scrubland spots in intensively managed agricultural areas. (3rd July 2016) - Canale, A.; Benvenuti, S.; Raspi, A.; Benelli, G.
Abstract : Insect pollinators of Rhamnus alaternus belong to 11 families, 17 genera and 20 species. The most abundant species is the honeybee followed by flies and bumblebees. Honeybee visits on R. alaternus decreased from late winter to early spring, highlighting the key role of this flowering in food paucity periods.